A retrospective analysis of the causes of postoperative ventral hernia recurrence - Piatnochka, V. I.; Kornaha, S. I.; Kohan, R. S. (Journal of Education, Health and Sport, 2019)
Considering the results of surgical treatment of postoperative ventral hernia, a significant number of recurrences of 4.3–46 % should be noted, and in case of large and giant postoperative ventral hernias reaches up to 80 %, which is associated with demographic imbalance that is an increase in the number of persons of old and senile age with comorbidity typical for them. Excessive obesity, especially in women, requires a revision of the main surgical approaches in the choice of methods of hernioplasty. Failure to take into account the present syndrome of undifferentiated connective tissue dysplasia (UCTD) in the performance of hernioplasty and allohernioplasty in 60 % of cases leads to postoperative relapse. Objective. On the basis of the analysis of the performed surgical treatment of patients with ventral and postoperative ventral hernia, to study the main causes of the development of recurrent hernia, which would improve the results of surgical treatment of this category of patients. Materials and methods. The clinical section of the work is based on a retrospective analysis of the results of surgical treatment of 1419 patients who underwent surgery on the anterior abdominal wall for primary ventral and postoperative ventral hernias. The distribution of patients into groups was according to the periods of surgical treatment of patients: from 2001 to 2009 and from 2010 to2017. In the first period, 597 (42.07%) patients who made the comparison group were examined and operated. The main group (2010–2017) amounted to 822 (57.93 %) patients. To determine the localization, size and extent of hernial bulging in defects of the anterior abdominal wall, we used the classification of the European Association of Surgeons-Herniologists (EHS-classification, 2008). In the comparison group, R1 was observed in 123 (93.18 %) patients, R2 – in 6 (4.55 %), R3 – in 2 (1.51%), R4 and more – in 1 (0.76 %). In the main group: R1 was observed in 63 (71.59 %) patients, R2 – in 18 (20.45 %), R3 – in 5 (5.68 %), R4 and more – in 2 (2.28 %). Results. In 250 (17.62 %) patients, recurrent hernia developed after various types of surgery. The highest recurrence rate was observed in patients after own tissue hernioplasty, which was 36.07 % of all operated patients according to this procedure. In second place, by the frequency of relapse were patients after performed allohernioplasty using inlay technique – 19.63 %. The recurrence rate after allohernioplasty by the onlay technique is, according to our study, 10.58 %. After performing the sublay technique, the results obtained differ significantly with a low percentage of relapses compared to other methods of hernioplasty. Thus, the recurrence was only in 6.01 % of cases. The only method of surgical treatment of POVH with no recurrence was the method of hernioplasty with anatomic separation of the components of the anterior abdominal wall (CST), which was performed in two variants – without the use of polypropylene mesh (PPM) by Ramirez and combined one using PPM. Such data may be explained by the small number of completed surgery interventions (45 (3.17%)) and short observation periods (4 years). Conclusions. Analyzing the causes of recurrence, it can be argued that the main ones are the choice of inadequate method of hernioplasty to a specific clinical situation, incomplete revision of the musculo-aponeurotic layer of the anterior wall, especially in patients with postoperative ventral hernias and concomitant undifferentiated connective tissue dysplasia and obesity, the presence of hidden (small in size and clinically intact) defects and weaknesses, incorrect choice of mesh implant type (“light” or “heavy” polypropylene mesh) and its size, choice of inappropriate material thickness.